A Comprehensive Approach to Detect Hybridization Sheds Light on the Evolution of Earth's Largest Lizards. (29th January 2021) - Pavón-Vázquez, Carlos J; Brennan, Ian G; Keogh, J Scott
Abstract: Hybridization between species occurs more frequently in vertebrates than traditionally thought, but distinguishing ancient hybridization from other phenomena that generate similar evolutionary patterns remains challenging. Here, we used a comprehensive workflow to discover evidence of ancient hybridization between the Komodo dragon ( Varanus komodoensis ) from Indonesia and a common ancestor of an Australian group of monitor lizards known colloquially as sand monitors. Our data comprise $>$ 300 nuclear loci, mitochondrial genomes, phenotypic data, fossil and contemporary records, and past/present climatic data. We show that the four sand monitor species share more nuclear alleles with $V$ . komodoensis than expected given a bifurcating phylogeny, likely as a result of hybridization between the latter species and a common ancestor of sand monitors. Sand monitors display phenotypes that are intermediate between their closest relatives and $V$ . komodoensis . Biogeographic analyses suggest that $V$ . komodoensis and ancestral sand monitors co-occurred in northern Australia. In agreement with the fossil record, this provides further evidence that the Komodo dragon once inhabited the Australian continent. Our study shows how different sources of evidence can be used to thoroughly characterize evolutionary histories that deviate from a treelike pattern, that hybridization can have long-lasting effects on phenotypes, and that detecting hybridization can improve our understanding of evolutionary and biogeographic patterns.[Biogeography; introgression; Komodo dragon; phylogenetic networks; phylogenomics; reticulation; Varanus. ]